The Relationship Between Self-Efficacy and Peer Conformity in Relation to Cheating Behavior Among Ninth-Grade Students - Dentamara La Viera Brilliany; Fajar Kawuryan (Golden Ratio of Social Science and Education, 2026)
Cheating cases remain a serious problem in the world of education in Indonesia. According to the 2024 Education Integrity Assessment Survey (SPI) published by the Corruption Eradication Commission (KPK) in April 2025, 78% of schools still engage in cheating behavior. This study aims to investigate the relationship between self-efficacy and peer conformity in relation to cheating behavior among grade IX students. This study used a quantitative method with a sampling technique, namely cluster random sampling, involving 100 respondents. Data were collected through paper questionnaires distributed directly, which utilized three Likert scales: the Cheating Behavior Scale (26 items), the Self-Efficacy Scale (15 items), and the Peer Conformity Scale (20 items). After testing the assumptions and hypotheses, the results revealed a highly significant relationship between self-efficacy and peer conformity with cheating behavior among students, with a p-value of 0.000 (p < 0.01). The minor hypothesis indicates a highly significant relationship between self-efficacy and cheating behavior (r = 0.887, p < 0.001) and between peer conformity and cheating behavior (r = 0.873, p < 0.001). This research can contribute to the educational environment, as influenced by psychological factors. This study aims to empirically investigate the relationship between self-efficacy and peer conformity in relation to cheating behavior among ninth-grade students. The findings of this study are expected to contribute to educational psychology by providing insight into factors related to cheating behavior.